A convergence study of phase-field models for brittle fracture. (15th October 2017) - Linse, Thomas; Hennig, Paul; Kästner, Markus; de Borst, René
Highlights: Boundary effects can cause discrepancies of numerical results for Gamma-convergence. Identifying phase field with irreversible damage prevents convergence to discrete crack length. Numerical results confirm the findings. Abstract: A crucial issue in phase-field models for brittle fracture is whether the functional that describes the distributed crack converges to the functional of the discrete crack when the internal length scale introduced in the distribution function goes to zero. Theoretical proofs exist for the original theory. However, for continuous media as well as for discretised media, significant errors have been reported in numerical solutions regarding the approximated crack surface, and hence for the dissipated energy. We show that for a practical setting, where the internal length scale and the spacing of the discretisation are small but finite, the observed discrepancy partially stems from the fact that numerical studies consider specimens of a finite length, and partially relates to the irreversibility introduced when casting the variational theory for brittle fracture in a damage-like format. While some form of irreversibility may be required in numerical implementations, the precise form significantly influences the accuracy and convergence towards the discrete crack.